Evaluating the impact of gender sensitivity training on public officers' attitudes - an empirical study. (2017) - Goel, Sangeeta
As more and more organisations have come to consider the short-term training a 'quick fix' for long persisting organisational problems like gender-based bias, it will be interesting to see if the resources invested in such 'quick fix' training yields desired results. In order to determine if such results were possible, a study was conducted, using participants with N = 220 in a gender sensitivity training (GST) program. The initial survey was a pre-test, administered before training and the second survey was administered after a ten-day GST module. The two datasets (pre and post GST) were collected and compared using bivariate statistical analysis. These results demonstrate that a gender sensitisation program of short duration could be of limited help in addressing such problems being embedded in personality and takes time to change. The paper raises a topical question if the resources engaged in these programs are well spent.